1986
DOI: 10.3354/meps032041
|View full text |Cite
|
Sign up to set email alerts
|

Importance of predatory infauna in marine soft-bottom communities: reply to Wilson

Abstract: Wllson (1986) has criticized the application of a 3-level interactive model, epibenthic predators -predatory infauna -other infauna, to marine soft-bottom communities. His model, though inexact, shows that preferential predation on predatory infauna by epibenthic predators is a requirement of the 3-level model. His reanalysis of the caging studies used to test the 3-level model, however, is unacceptable as it analyzes only 32 % of the original data set and ignores predat~on by omnivores which is known to be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The evidence presented here is by no means exhaustive, but provides strong support for a 3-level trophic structure model in sedimentary habitats. Our results also extend the validity of this model to sandy sediments, a habitat where Ambrose (1984aAmbrose ( , 1986) and subsequent authors have not found supporting evidence for this model. The consistency of these results is also remarkable considering that they come from contrasting habitats (15 to 30 m deep coarse sandy sediments in Newfoundland and intertidal muddy-sand sediments in Prince Edward Island), and from the manipulation of either an entire guild of predators (exclusions) or individual epibenthic predators (snow crab, green crab, rock crab) in the laboratory or in the field.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The evidence presented here is by no means exhaustive, but provides strong support for a 3-level trophic structure model in sedimentary habitats. Our results also extend the validity of this model to sandy sediments, a habitat where Ambrose (1984aAmbrose ( , 1986) and subsequent authors have not found supporting evidence for this model. The consistency of these results is also remarkable considering that they come from contrasting habitats (15 to 30 m deep coarse sandy sediments in Newfoundland and intertidal muddy-sand sediments in Prince Edward Island), and from the manipulation of either an entire guild of predators (exclusions) or individual epibenthic predators (snow crab, green crab, rock crab) in the laboratory or in the field.…”
Section: Resultssupporting
confidence: 83%
“…Quijón & Snelgrove 2005a,b). As in the original studies by Ambrose (1984aAmbrose ( , 1986 and references therein) and Wilson (1986), we compare simple metrics such as the ratio of predators: non-predators in sediments exposed to predation and those that are not.…”
Section: Abstract: Trophic Complexity · Predatory Infauna · Soft Sedmentioning
confidence: 99%
“…Predators can affect prey populations directly through reducing prey abundance or biomass (e.g., Hairston et al 1960, Paine 1966, Connell 1972, or indirectly through altering how a prey species interacts with its competitor (Paine 1966, Hughes 1994, Werner and Anholt 1996 or its own prey (Carpenter et al 1985, Power et al 1985, Ambrose 1986). In addition to these density-mediated (direct and indirect) effects where one species influences the abundance or biomass of one or several other species, a species can also mediate trophic interactions through behavioral, chemical, and environmental pathways (Wootton 1993, Menge 1995.…”
Section: Introductionmentioning
confidence: 99%
“…He proposed a 3-level interactive model composed of epibenthic predators, predatory infauna and other infauna. There is increasing evidence that the predatory infauna structures soft bottom communities (Kent & Day 1983, Commito & Ambrose 1985a, b, Comnlito & Shrader 1985, Ambrose 1986, Schubert & Reise 1986, and these studies emphasize the complexities of community organization in soft bottoms rather than providing clear cut principles.…”
Section: Introductionmentioning
confidence: 99%